2019
DOI: 10.1002/chem.201902663
|View full text |Cite
|
Sign up to set email alerts
|

Five‐Membered Ruthenacycles: Ligand‐Assisted Alkyne Insertion into 1,3‐N,S‐Chelated Ruthenium Borate Species

Abstract: Buildingu pon previous work, the chemistry of [(h 6 -p-cymene)Ru{P(OMe) 2 OR}Cl 2 ], (R = Ho rMe)h as been extended with [H 2 B(mbz) 2 ] À (mbz = 2-mercaptobenzothiazolyl) using different Ru precursors and borate ligands. As ar esult,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 99 publications
0
28
0
Order By: Relevance
“…70 4). 2,71,73,74,76 These alkenylboranes are believed to be the intermediates in the formation of vinylborane species. The solid-state structure of 41b confirmed that the hydroboration of the alkyne occurred via Markovnikov addition in which the olefinic unit (MeO 2 C−CCH 2 ) is coordinated to the Ru center in an η 2 fashion (Figure 8a).…”
Section: Hydroboration Reactionsmentioning
confidence: 99%
See 4 more Smart Citations
“…70 4). 2,71,73,74,76 These alkenylboranes are believed to be the intermediates in the formation of vinylborane species. The solid-state structure of 41b confirmed that the hydroboration of the alkyne occurred via Markovnikov addition in which the olefinic unit (MeO 2 C−CCH 2 ) is coordinated to the Ru center in an η 2 fashion (Figure 8a).…”
Section: Hydroboration Reactionsmentioning
confidence: 99%
“…The solid-state structures of 51a and 52a show five-membered metallacycles with exo CC double bonds, and the complexes can be considered structural isomers. 2 The five-membered ring in 51a contains a nonplanar Ru−C−N−C−S unit, while a planar Ru−C−S−C−N unit exists in 52a. Initial activation of the alkyne followed by proton transfer from the alkyne unit to an N,S-benzothiazolyl group likely resulted in the formation of 51a and 52a.…”
Section: Hydroboration Reactionsmentioning
confidence: 99%
See 3 more Smart Citations